The impact of an intervention programme on the decision making speed and accuracy, declarative knowledge, and selected visual skills of u/20 rugby players - Uys, Stefanie (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Sport Science))--Stellenbosch University, 2008.